A Review of the Literature: The Needs of Nontraditional Students in Postsecondary Education. Issue 4 (3rd January 2018) - MacDonald, Kris
Abstract : Nontraditional students, or adult learners, are the new majority in the classroom in any sector of higher education according to the National Center for Education Statistics. These students are considered nontraditional if they identify with at least one of the following criteria: be at least 25 years old, attend school part‐time, work full‐time, be a veteran, have children, wait at least one year after high school before entering college, have a GED instead of a high school diploma, being a first‐generation student (FGS), are enrolled in nondegree programs, or have reentered a college program. This population also tends to be predominantly female. As this population trend grows exponentially in higher education, it is imperative for administrators and instructors to learn how to work with these students, as they deal with far different struggles to stay in school than their traditional counterparts. This review of the current literature will explore the best practices for what nontraditional students need based on the varied issues they face in reentering a classroom. A lack of knowledge about this population has led to low enrollment rates and high attrition rates, leaving some schools especially in the for‐profit sector, struggling to stay afloat. It is imperative that as populations shift, so do pedagogical and supportive approaches within postsecondary institutions in order to retain these students and ensure their academic success.